2021
DOI: 10.3389/fenvs.2021.743894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lockdown on Pollutant Levels in the Delhi Megacity: Role of Local Emission Sources and Chemical Lifetimes

Abstract: The COVID-19 pandemic resulted in changed emission regimes all over the world. India also imposed complete lockdown on all modes of travel and industrial activities for about 2 months from 25-March-2020 and later unlocked these activities in a phased manner. Here, we study signatures of emissions changes on levels of atmospheric trace gases and aerosols contributing to air pollution over multiple sites in India’s capital Delhi covering various lockdown and unlock phases using satellite data and in-situ observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…This time is coincident with the peak second wave of COVID-19 in India when states had imposed restrictions on the movement of vehicles. Mahato et al ( 2020 ) and Mallik et al ( 2021 ) observed a similar lockdown-period improvement in air quality over Delhi, otherwise one of the most polluted cities in India. Rajesh and Ramachandran ( 2022 ) found a 35% reduction in equivalent black carbon over Ahmedabad, which in turn reduced the aerosol radiative forcing over this location.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This time is coincident with the peak second wave of COVID-19 in India when states had imposed restrictions on the movement of vehicles. Mahato et al ( 2020 ) and Mallik et al ( 2021 ) observed a similar lockdown-period improvement in air quality over Delhi, otherwise one of the most polluted cities in India. Rajesh and Ramachandran ( 2022 ) found a 35% reduction in equivalent black carbon over Ahmedabad, which in turn reduced the aerosol radiative forcing over this location.…”
Section: Resultsmentioning
confidence: 73%
“…Several studies have reported the decline in atmospheric pollutants over India during the national lockdown. Mallik et al ( 2021 ) reported a significant decrease in the levels of several air pollutants in Delhi. Jain et al ( 2021 ) reported a decline in trace gases and particulate matter over Gadanki, a tropical rural setting in southern India.…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing the air quality index (AQI) and its various components (O 3 , CO, NO 2 , PM 10 and PM 2.5 ) over Delhi during the second wave of COVID-19, we arrived at a meaningful inference on the pivotal role of air pollutants in worsening the critical condition due to COVID-19. A recent study [18] also reported an enhanced surface ozone level during the lockdown period in 2020 over Delhi. Figure 2 shows the variation in the AQI with the mortality rate during the peak phase of the second wave.…”
Section: Observed Pollution and Its Relation To Covid-19 Mortalitymentioning
confidence: 87%
“…Pandemic-related travel and activity restrictions led to a global 'anthropause' (Rutz et al 2020b) which, in many areas, translated into a decrease in human pressures on ecosystems and in the exploitation of natural resources. From 2020, studies began to highlight reductions in human activities and improvements in water quality in coastal zones throughout the world (review from Mallik et al 2021). Among those, lower noise pollution was observed along a ferry lane in Scandinavia (De Clippele and Risch 2021), and higher fish abundances were linked to decreased fishing activities in the Gulf of Mannar, India (Patterson Edward et al 2021).…”
Section: Introductionmentioning
confidence: 99%